Pediatric in-hospital emergencies: real life experiences, previous training and the need for training among physicians and nurses - Lehmann, Ronny; Seitz, Anke; Meyburg, Jochen; Hoppe, Bettina; Hoffmann, Georg F.; Tönshoff, Burkhard; Huwendiek, Sören (BMC Research Notes, 2019)
Pediatric emergencies challenge professional teams by demanding substantial cognitive effort, skills and effective teamwork. Educational designs for team trainings must be aligned to the needs of participants in order to increase effectiveness. To assess these needs, a survey among physicians and nurses of a tertiary pediatric center in Germany was conducted, focusing on previous experience, previous training in emergency care, and individual training needs.
Gesehen am 12.11.2019